Breathlessness measurement should be standardised for the level of exertion. Issue 5 (31st May 2018) - Beaumont, Marc; Mialon, Philippe; Couturaud, Francis
We would like to thank M. Ekström and colleagues for their correspondence with comments on our article entitled "Effects of inspiratory muscle training on dyspnoea in severe COPD patients during pulmonary rehabilitation: a controlled randomised trial" [1]. We agree with most of the points underlined by M. Ekström and colleagues. Dyspnoea should be measured at a standardised level of exertion http://ow.ly/kpMQ30jWXau